(5x-1)(x+2)=8x-4

Simple and best practice solution for (5x-1)(x+2)=8x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x-1)(x+2)=8x-4 equation:


Simplifying
(5x + -1)(x + 2) = 8x + -4

Reorder the terms:
(-1 + 5x)(x + 2) = 8x + -4

Reorder the terms:
(-1 + 5x)(2 + x) = 8x + -4

Multiply (-1 + 5x) * (2 + x)
(-1(2 + x) + 5x * (2 + x)) = 8x + -4
((2 * -1 + x * -1) + 5x * (2 + x)) = 8x + -4
((-2 + -1x) + 5x * (2 + x)) = 8x + -4
(-2 + -1x + (2 * 5x + x * 5x)) = 8x + -4
(-2 + -1x + (10x + 5x2)) = 8x + -4

Combine like terms: -1x + 10x = 9x
(-2 + 9x + 5x2) = 8x + -4

Reorder the terms:
-2 + 9x + 5x2 = -4 + 8x

Solving
-2 + 9x + 5x2 = -4 + 8x

Solving for variable 'x'.

Reorder the terms:
-2 + 4 + 9x + -8x + 5x2 = -4 + 8x + 4 + -8x

Combine like terms: -2 + 4 = 2
2 + 9x + -8x + 5x2 = -4 + 8x + 4 + -8x

Combine like terms: 9x + -8x = 1x
2 + 1x + 5x2 = -4 + 8x + 4 + -8x

Reorder the terms:
2 + 1x + 5x2 = -4 + 4 + 8x + -8x

Combine like terms: -4 + 4 = 0
2 + 1x + 5x2 = 0 + 8x + -8x
2 + 1x + 5x2 = 8x + -8x

Combine like terms: 8x + -8x = 0
2 + 1x + 5x2 = 0

Begin completing the square.  Divide all terms by
5 the coefficient of the squared term: 

Divide each side by '5'.
0.4 + 0.2x + x2 = 0

Move the constant term to the right:

Add '-0.4' to each side of the equation.
0.4 + 0.2x + -0.4 + x2 = 0 + -0.4

Reorder the terms:
0.4 + -0.4 + 0.2x + x2 = 0 + -0.4

Combine like terms: 0.4 + -0.4 = 0.0
0.0 + 0.2x + x2 = 0 + -0.4
0.2x + x2 = 0 + -0.4

Combine like terms: 0 + -0.4 = -0.4
0.2x + x2 = -0.4

The x term is 0.2x.  Take half its coefficient (0.1).
Square it (0.01) and add it to both sides.

Add '0.01' to each side of the equation.
0.2x + 0.01 + x2 = -0.4 + 0.01

Reorder the terms:
0.01 + 0.2x + x2 = -0.4 + 0.01

Combine like terms: -0.4 + 0.01 = -0.39
0.01 + 0.2x + x2 = -0.39

Factor a perfect square on the left side:
(x + 0.1)(x + 0.1) = -0.39

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| -4+6s=6s | | 0=4k-4k | | -z+z=0 | | -8w=-6-7w | | 5c+6=5c | | 9x^2+6x+2=-6x-2 | | -d-4d=-5d | | 3x^2-12x+35=0 | | -4=-6v+4(v-5) | | -6+8u=8u | | 107-u=214 | | 19=-3y+8(y+8) | | 3x+4=2x+4+x | | 4r+8=3r | | 28=19m+12-11m | | 2-2j=-2j | | 7(1[u-3]1)+3u=19 | | 8(w+3)+7w=-21 | | 2/5(3x+1)=5/2(2x-1) | | 3t=4t-t | | x^2+50x-300=0 | | 3x=2x+31 | | 0=2x^4+x^3+8x-16 | | 3x-6=74-7x | | 400=21m-2 | | x^2+50x+30=0 | | 1/3(5x-1)=7x-2 | | 6w+2w-6w+1=19 | | 3(x+4)/4=5x-1/6 | | 18c+5c-22c-1=7 | | 2x+3/5=5x-1/2 | | 40-7x=12+3x |

Equations solver categories